Psychosocial Outcomes 3 to 10 Years After Donation in the Adult to Adult Living Donor Liver Transplantation Cohort Study (A2ALL) - Dew, Mary Amanda (Transplantation, 2016)
BACKGROUND: Studies of liver donors’ psychosocial outcomes focus on the short-term and rely largely on quality-of-life measures not specific to donation. We sought to examine long-term donation effects on three psychosocial domains: perceived physical, emotional, and socioeconomic outcomes. METHODS: Individuals donating 3–10 years previously at nine centers were eligible for telephone surveys. Survey responses were examined descriptively. Cluster analysis was used to identify distinct donor groups based on response profiles across psychosocial domains. Potential predictors of response profiles were evaluated with regression analysis. RESULTS: 517 donors (66%) participated (M=5.8 years postdonation, SD=1.9). 15%–48% of donors endorsed current donation-related physical health problems and concerns, and 7%–60% reported socioeconomic concerns (e.g., insurance difficulties, financial expenditures). However, on average, donors experienced high psychological growth, and 90% felt positively about donation. Cluster analysis revealed five donor groups. One group showed high psychological benefit, with little endorsement of physical or socioeconomic concerns (15% of donors). Four groups showed less favorable profiles, with varying combinations of difficulties. The largest such group showed high endorsement of physical concerns and financial expenditures, and only modest psychological benefit (31% of donors). Men and non-Hispanic whites were most likely to have unfavorable response profiles (p<.01). Compared with donors aged 19–30, older donors were less likely to have unfavorable profiles; these differences were significant for donors aged >40–50 (p’s<.008). CONCLUSIONS: Even many years postdonation, donors report adverse physical and socioeconomic effects, but positive emotional effects as well. Identification of response profiles and predictors may improve targeting of postdonation surveillance and care.